MICROVASCULAR ANGINA "X SYNDROME" CLINICAL SIGNS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Anatomical, physiological and histological structure of the heart. Connection with other ischemic heart diseases. Microvascular angina is different from other angina. Control of the heart through the blood and nervous system. How does microvascular angina have a negative effect on other diseases. Origin of angina pectoris among the population. Functional and morphological changes of microvascular angina and measures to prevent this disease.